Thermodynamic calculations of oxygen self-diffusion in mixed-oxide nuclear fuels. Issue 78 (4th August 2016) - Parfitt, D. C.; Cooper, M. W. D.; Rushton, M. J. D.; Christopoulos, S.-R. G.; Fitzpatrick, M. E.; Chroneos, A.
Abstract : Molecular dynamics calculations are used to provide a self-consistent prediction of the elastic, thermal expansion and oxygen self-diffusion properties of mixed oxide nuclear fuels at arbitrary compositions. Abstract : Mixed-oxide fuels containing uranium with thorium and/or plutonium may play an important part in future nuclear fuel cycles. There are, however, significantly less data available for these materials than conventional uranium dioxide fuel. In the present study, we employ molecular dynamics calculations to simulate the elastic properties and thermal expansivity of a range of mixed oxide compositions. These are then used to support equations of state and oxygen self-diffusion models to provide a self-consistent prediction of the behaviour of these mixed oxide fuels at arbitrary compositions.